Synthesis of polymeric materials for antibacterial and antibiofilm applications - Li, Jianghua (Nanyang Technological University, 2020)
Antimicrobial resistance has become a global healthcare crisis. Compounded with the evolution of multi-drug resistance, bacteria also develop biofilms to protect themselves, so that biofilm-associated infections are extremely difficult to treat. Antibiotics can be up to 1000-fold less effective to biofilms as compared with the planktonic form. Once developed into the biofilm form, it will become highly resistant to conventional antibiotics. Many antibiotics, natural antimicrobial peptides (AMPs) and synthetic antimicrobial agents have been studied as antibiofilm agents, but the general efficacy is still not high. Further, they usually suffer from the problem of toxicity and limited life span. In this thesis, two series of novel antibiofilm cationic polymeric nanoparticles (NPs) have been developed to show excellent biofilm removal capability. Firstly, I synthesized polysaccharide-based polymeric NPs made from dextran-block-(poly((3-acrylamidopropyl) trimethylammonium chloride (AMPTMA)-co-butyl methacrylate (BMA)) (DA95B5). Interestingly, this amphiphilic copolymer DA95B5 self-assembled into NP form which did not have any antibacterial effect but exhibited excellent preformed biofilm removal ability. The antifouling shell of the polysaccharide as well as the NP form, enhanced the biofilm dispersal ability by a mechanism termed “nanoscale bacterial debridement”. Cryo-transmission electron microscope (cryo-TEM) and confocal microscopy showed that these NPs can penetrate into the biofilm and form a coating around the negatively charged bacteria to weaken the cell-biofilm matrix interaction. In vitro results showed that the polymeric NPs exhibited antibiofilm ability towards several multi-drug resistant (MDR) and clinically relevant Gram-positive bacterial strains, with efficacy much higher and/or similar to the conventional standard antibiotics. In vivo data corroborated that such NPs possess methicillin-resistant S. aureus (MRSA) biofilm removal efficacy that was higher than vancomycin. Further, both in vitro and in vivo data showed NPs have good biocompatibility with low hemolysis and cytotoxicity. This is the first report of a synthetic intrinsically antibiofilm dispersing agent in contrast to many other such agents which are enzyme-based. I also presented a novel system (named as FTP NPs) made from biocompatible F-127 surfactant, tannic acid (TA) and biguanide-based polymetformin (PMET), with good antibacterial and antibiofilm activity against MRSA both in vitro and in vivo. FTP NPs outperformed PMET with around 2-fold more log10 reduction of the MRSA biofilm bacterial cell counts at low concentrations (8-32 µg/mL) in vitro, which may due to the antifouling property from the hydrophilic polyethylene glycol (PEG) chain of F-127. Further, in an in vivo murine excisional wound model, FTP NPs achieved 1.8 log10 reduction of biofilm-associated MRSA bacteria, which significantly outperform that of vancomycin (0.8 log10 reduction). Moreover, in vitro cytotoxicity tests showed FTP NPs has less toxicity than PMET towards mammalian cells; and the in vivo data showed that FTP NPs exhibited no acute toxicity to mice with negligible body weight loss and small variation of blood biomarkers at 10 mg/kg via the intravenous injection. These biguanide-based NPs can serve as promising antibiofilm agents against MRSA-associated infections. Overall, both of these biofilm removal platforms provide exciting opportunities for treatment of multi-drug resistant biofilm infections which may have widespread applications.